Long-lasting intense cut-off lows to become more frequent in the Northern Hemisphere - Aditya N. Mishra; Douglas Maraun; Reinhard Schiemann; Kevin Hodges; Giuseppe Zappa; Albert Ossó (Communications Earth & Environment)
Abstract Cut-off Lows are slow-moving mid-latitude storms that are detached from the main westerly flow and are often harbingers of heavy and persistent rainfall. The assessment of Cut-off Lows in climate models is relatively limited, in fact, there are no studies conducted on the future changes of Cut-off Lows within climate models. Given the importance of Cut-off Lows in leading to severe hazards, here we study them in Coupled Model Intercomparison Project Phase 6’s worst-case future simulations (SSP5-8.5). Most (80%) of the models show that Cut-off Lows with high intensity and longer lifetimes are projected to become more frequent in spring over the land regions of the Northern Hemisphere. Such an increase in Cut-off Low frequency could substantially increase related potential hazards. An increase in Cut-off Low propagation velocity, however, may partly offset this increase in hazard. Lastly, projected changes in the jet stream with possible dynamical linkages to Cut-off Lows corroborate the findings of this study.